Fishes (Osteichthyes: Actinopterygii) from the Penacho stream, upper Paraná River basin, Paraná state, Brazil - Alexandro Costa; Dhiego Ferreira; Wilson Silva; Augusto Zanatta; Oscar Shibatta; Bruno Galindo (Check List, 2013)
The focus of this work was to survey the ichthyofauna of the Penacho stream, a tributary of the Laranjinha River, northeastern Paraná State, in an area of the Upper Paraná River basin still devoid of ichthyofaunal studies. In general, the banks of the Penacho Stream are predominantly characterized by pasture or agricultural activities and may exhibit little riparian vegetation in few stretches. Fishes were collected at eight different locations, from its headwaters to its mouth, between February 2009 to March 2010. A total of seven orders, twelve families and thirty-three species, three of which not native to the basin, were reported. The fish species captured along the Penacho stream are those that still manage to stay in those environments, even in changed conditions. However, to better understand the effects of degradation on fish diversity, it is necessary to monitor it along time.